2022
DOI: 10.1101/2022.09.19.508543
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expression of thioredoxin-1 in the ASJ neuron corresponds with and enhances intrinsic regenerative capacity under lesion conditioning inC. elegans

Abstract: A conditioning lesion of the peripheral sensory axon triggers robust central axon regeneration in mammals. We visualize the ASJ neuron of C. elegans with a cell-specific green fluorescent protein reporter driven by a thioredoxin trx-1 promoter and trigger conditioned regeneration by laser surgery or genetic disruption of sensory pathways. Utilizing calibrated fluorescent beads, we demonstrate that these neurons brighten when conditioned, suggesting that trx-1 expression indicates regenerative capacity. We show… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Our laboratory studies neuroregeneration and, in a parallel study, identified that the expression of the gene, thioredoxin-1 (TXN/ trx-1 ), roughly correlates with regenerative capacity. 24 A fluorescent GFP reporter of trx-1 potentially allows high-throughput screening of regeneration genes without time-consuming surgery needed in previous studies. We are specifically interested in genes underlying lesion-conditioned regeneration, 25 which is distinct from other forms of neuronal regeneration mediated by the well-studied gene dual leucine zipper kinase DLK/ dlk-1 .…”
Section: Resultsmentioning
confidence: 99%
“…Our laboratory studies neuroregeneration and, in a parallel study, identified that the expression of the gene, thioredoxin-1 (TXN/ trx-1 ), roughly correlates with regenerative capacity. 24 A fluorescent GFP reporter of trx-1 potentially allows high-throughput screening of regeneration genes without time-consuming surgery needed in previous studies. We are specifically interested in genes underlying lesion-conditioned regeneration, 25 which is distinct from other forms of neuronal regeneration mediated by the well-studied gene dual leucine zipper kinase DLK/ dlk-1 .…”
Section: Resultsmentioning
confidence: 99%